«A school gives knowledge. Knowledge gives strength. Strength gives power...»: on the history of the activities of the Borys Grinchenko «Prosvita» Society in the Salzwedel camp for Ukrainian captives in Germany (1916-1917) - Sribniak, Ihor (Educological discourse, 2022)
The article reveals the specifics of the activities of the Borys Grinchenko «Prosvita» Society,which led to the establishment of the People’s School with the same name in the Salzwedel camp (Germany). The initial phase of its activity was marked by significant difficulties due to the reluctance of some captives to visit it due to fear of reprisals from the Russian tsarism (after their returning home). But in consequence to the explanatory work of the members of the Educational Department Union for the Liberation of Ukraine and the Ukrainian most active members in the camp, this fear was overcome, after which the number of students began to increase steadily. During 1916-1917, hundreds of Ukrainian captives graduated from the Borys Grinchenko People’s School, who received not only basic knowledge (writing, reading, arithmetic) within its walls, but also gained the understanding of many phenomena of political and social life and, in addition, mastered the basics of agronomic and exact sciences. The school initiated profound changes in their consciousness, making school graduates an integral part of the Ukrainian world, the political component of which was mercilessly persecuted in Russia, and therefore forced to choose their «place under the sun» on German soil. The Borys Grinchenko People’s School became one of the most powerful system-forming national factors in the camp, which created the Ukrainian environment through its very work. Within its walls - sometimes even against their will – the prisoners began to realize the injustice of the socio-political order in tsarist Russia and to understand the ultimate need to separate Ukraine from the imperial centre with its subsequent acquisition of the sovereign status. In this way, all the time the School and its pedagogical staff significantly participated in the process of forming the national-state worldview of those Ukrainian captives who sought education, fully fulfilling their patriotic duty to their Motherland.